2008
DOI: 10.1016/j.ejvs.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular and Open Approaches to Non-thrombosed Popliteal Aneurysm Repair: A Meta-analysis

Abstract: Endovascular repair of popliteal artery aneurysms offers similar medium-term benefits as an open repair. However, short-term graft thrombosis and reintervention rates are significantly greater. With the current technology it is difficult to justify endovascular treatment of popliteal aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 32 publications
0
22
1
2
Order By: Relevance
“…11 This trend could be questioned on the basis the results of this study. 11,12 For the first time it has been possible to Figure 3. Flow chart of treatment given in the subgroup treated for acute ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…11 This trend could be questioned on the basis the results of this study. 11,12 For the first time it has been possible to Figure 3. Flow chart of treatment given in the subgroup treated for acute ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…[13]. Lovegrove et al in a recent meta-analysis reported that endovascular repair of PAAs offers similar medium-term benefits but higher rates of early graft thrombosis and early interventions compared to open repair [14]. It is clear that although different case series [15, 16] and reports suggest the utility and technical success of endoluminal approach, long-term patency rates of endovascular repair of PAAs are still awaited.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,15,19,[35][36][37][38][39][40] Several studies have reported complications including thrombosis, endoleaks, stent migration and stent fractures, which can be as high as 9.60% in the case of type 2 endoleaks, although the great majority are self-limiting and do not lead to expansion of the aneurysm sac. 24,39,41 Previous studies have reported higher rates of reintervention after ES, which was not the case in our series, 9 probably because of the small number of ES and the short follow-up. These rates are the reason why careful monitoring of patients who have undergone popliteal aneurysm repair is necessary, whether treated with endovascular or open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic aneurysms smaller than 2.0 cm and diameter without thrombus are monitored periodically using Doppler ultrasound. 8,9 Open surgery is most widely employed and the preferred technique is a bypass, using a medial approach, proximal and distal ligature of the aneurysm and an inverted great saphenous vein graft. As endovascular techniques develop, new approaches to management of popliteal aneurysms are being studied, in the hope of achieving lower complication rates.…”
Section: Introductionmentioning
confidence: 99%